2017
DOI: 10.1080/19420889.2017.1395119
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational maturation of IDA, a peptide signal controlling floral organ abscission in Arabidopsis

Abstract: The abscission of sepals, petals and stamens in Arabidopsis flowers is controlled by a peptide signal called IDA (Inflorescence Deficient in Abscission). IDA belongs to the large group of small post-translationally modified signaling peptides that are synthesized as larger precursors and require proteolytic processing and specific side chain modifications for signal biogenesis. Using tissue-specific expression of proteinase inhibitors as a novel approach for loss-of-function analysis, we recently identified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Surprisingly, however, the abscission‐inducing activity of IDA was indistinguishable for the hydroxylated and non‐hydroxylated forms of the mature peptide (Stührwohldt et al . ). In order to explain this obvious discrepancy, we speculate that mIDA may become hydroxylated after being taken up by the plant.…”
Section: Proline Hydroxylationmentioning
confidence: 97%
“…Surprisingly, however, the abscission‐inducing activity of IDA was indistinguishable for the hydroxylated and non‐hydroxylated forms of the mature peptide (Stührwohldt et al . ). In order to explain this obvious discrepancy, we speculate that mIDA may become hydroxylated after being taken up by the plant.…”
Section: Proline Hydroxylationmentioning
confidence: 97%
“…The presence of this signal peptide in the sequence of all identified genes suggests a mechanism of posttranslational maturation in the apoplast similar to that described in Arabidopsis, where the prepropeptide is proteolytically processed by subtilisin-like serine proteinases to yield a bioactive peptide [29]. This cleavage that occurs between positions 6 and 7 of the EPIP motif [30], normally occupied by a K and a G respectively, leaves a bioactive peptide of 14 amino acids containing the PIP motif with G7 as N-terminal and N20 as C-terminal residues (Figure 2).…”
Section: Expression Patterns Of Ida-like Genes In Nicotiana Benthamiamentioning
confidence: 57%
“…The Arabidopsis IDA precursor protein is secreted into the apoplast where it is processed into a smaller peptide ( Stenvik et al , 2008 b ; Butenko and Simon, 2015 ; Schardon et al , 2016 ). The secreted IDA protein is predicted to be cleaved by subtilisin-like serine proteinases at both the N-terminus and C-terminus resulting in a 14 amino acid bioactive product (GVPIPPSAPSKRHN) ( Schardon et al , 2016 ; Stührwohldt et al , 2017 ). When the N-terminal cleavage site was blocked with N-methylation of the Lys/Gly bond in a longer 23 amino acid peptide (SHIFGYLPK[m]GVPIPPSAPSKRHN), the methylated peptide was completely inactive whereas the non-methylated 23 amino acid peptide retained activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, others have demonstrated that the ida mutant phenotype could be rescued with IDA-like peptides that do not contain a hydroxyproline modification ( Stenvik et al , 2008 b ; Schardon et al , 2016 ). Interestingly, a recent report argues that the exogenously applied peptides might still be hydroxylated at proline by an extracellular enzyme ( Stührwohldt et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%